2002
DOI: 10.1111/j.1834-7819.2002.tb00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Dilemmas Confronting Dentists in Queensland, Australia

Abstract: Background: This paper details contemporary ethical dilemmas encountered by Queensland dentists. Methods: An age-stratified sample of 499 dentists resident in Queensland was surveyed. The questionnaire contained scenarios of five common ethical dilemmas.In addition, open-ended questions sought the respondent's most frequent, difficult and recent ethical dilemmas, and where they would seek guidance in dealing with ethical problems. Results: Respondents acknowledged the patient's rights in treatment decisions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 19 publications
1
21
3
Order By: Relevance
“…Given that 85% of dental practitioners work in the private sector, and that even insured patients may face high out of pocket costs, this result is not surprising. International commentary suggests that cost‐related concerns and over‐servicing are more common in fee‐for‐service systems, whereas under‐treatment tends to arise in capitated practices . Regardless of the cause, these findings raise important ethical issues for the dental profession insurers and government funders.…”
Section: Discussionmentioning
confidence: 99%
“…Given that 85% of dental practitioners work in the private sector, and that even insured patients may face high out of pocket costs, this result is not surprising. International commentary suggests that cost‐related concerns and over‐servicing are more common in fee‐for‐service systems, whereas under‐treatment tends to arise in capitated practices . Regardless of the cause, these findings raise important ethical issues for the dental profession insurers and government funders.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies have shown that the physicians, dentists, and nurses have appreciated the importance of knowledge of ethics, but the majority of studies have shown poor knowledge of ethics and health law which has resulted in a violation of ethical principles. [ 3 14 15 16 17 18 19 ] Contrastingly, some of the studies have reported good to fair knowledge among dental professionals. [ 18 20 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] In the past few decades, the balance of decision-making in determining what is the “best” treatment has shifted from professional paternalism toward respecting the informed and autonomous decision of the patient. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Planning and carrying out excessive treatment was one of the five factors Christensen offered on why the public’s attitude toward the credibility of dentists may be changing [ 36 ]. Overtreatment is also one aspect of the first broad category of ethical concern within the dental profession identified by the Queensland survey, that is, problems arising from the quality of care provided by other members of the profession, including under- and over-servicing and apparently substandard treatment [ 37 ].…”
Section: Discussionmentioning
confidence: 99%